Two new mountain lizard species of the Phymaturus genus (Squamata: Iguania) from northwestern Patagonia, Argentina - Avila, Luciano Javier (Zootaxa, 2011)
Two new species of lizards of the saxicolous and viviparous genus Phymaturus from Patagonia are described. The new species are members of the Phymaturus patagonicus species group distributed only in volcanic plateaus and mountains of southern Argentina. Phymaturus sitesi sp. nov. differs from all other members of the patagonicus group in its unique dorsal pattern of small white spots on a light-gray to brown-gray background and allopatric geographical distribution. Absence of sexual dichromatism differentiated Phymaturus sitesi sp. nov. from P. payuniae, P. zapalensis, and P. delheyi n. sp. , and the midbody scales count differentiated from the P. delheyi sp. nov. and P. nevadoi (with some overlap). Also Phymaturus sitesi sp. nov. presents lower count in the ventral scales than in P. delheyi sp. nov. Phymaturus delheyi sp. nov. can be distinguished from other species of the patagonicus group by unique dorsal pattern of medium size white spots on a dark-brown background and allopatric distribution. The presence of sexual dichromatism differentiates Phymaturus delheyi sp. nov. from P. sitesi sp. nov. and P. nevadoi. Scales around midbody differentiated Phymaturus delheyi sp. nov. from P. payuniae and P. sitesi sp. nov. Also ventral scale count differentiated Phymaturus delheyi sp. nov. from P. sitesi sp. nov. and P. nevadoi (with some overlap).